Antibacterial performance of Ag Nanoparticles and AgGO nanocomposites prepared via rapid microwave-assisted synthesis method - Chook, S.W.; Chia, C.H.; Zakaria, S.; Ayob, M.K.; Chee, K.L.; Huang, N.M.; Neoh, H.M.; Lim, H.N.; Jamal, R.; Rahman, R.M.R.A. (2012)
Silver nanoparticles and silver-graphene oxide nanocomposites were fabricated using a rapid and green microwave irradiation synthesis method. Silver nanoparticles with narrow size distribution were formed under microwave irradiation for both samples. The silver nanoparticles were distributed randomly on the surface of graphene oxide. The Fourier transform infrared and thermogravimetry analysis results showed that the graphene oxide for the AgNP-graphene oxide (AgGO) sample was partially reduced during the in situ synthesis of silver nanoparticles. Both silver nanoparticles and AgGO nanocomposites exhibited stronger antibacterial properties against Gram-negative bacteria (Salmonella typhi and Escherichia coli) than against Gram-positive bacteria (Staphyloccocus aureus and Staphyloccocus epidermidis). The AgGO nanocomposites consisting of approximately 40 wt. silver can achieve antibacterial performance comparable to that of neat silver nanoparticles.